IoT applied to Environmental Monitoring in Oysters' Farms - Viegas, Vítor (2019)
The authors acknowledge to the project "OSTRAQUAL Enhancing and promoting the oyster aquaculture quality in Sado and Mira region", ref. 023838/SAICT/02/2016, for the financial support given by POR Lisboa, POR Alentejo 2020 and POR CRESC Algarve 2020 under FEDER, and by Fundacao para a Ciencia e Tecnologia.